The impact of smoking cessation attempts on stress levels - Seong-Jun Kim; Wonjeong Chae; Woo-Hyun Park; Min-Ho Park; Eun-Cheol Park; Sung-In Jang (BMC, 2019)
Abstract Background Cigarette smoking is a major health risk, particularly in male South Koreans. Smoking cessation can benefit health; however, the process of quitting smoking is difficult to some smokers and shows its relationship to their stress level. The hypothesis of this study is that who has failed attempts to stop smoking induce more stress than habitual smoking. Methods To test this, the analysis on the association between smoking cessation attempts and stress levels in smokers was performed. The Korean Community Health Survey (2011-2016) data with the total of 488,417 participants' data were used for this study. Survey data were analyzed using the chi-square test and logistic regression. As the dependent variable, self-reported level of stress was selected. Results Of the subject population, 78.3% (63.3% males, 81.4% females) felt stressed. Among participants who successfully stopped smoking, 73.0% (72.6% males, 78.1% females) reported feeling stressed. In contrast, of those who failed to stop smoking, 83.3% (83.6% males, 86.3% females) reported high stress levels. Among those who did not attempt smoking cessation, 81.1% (81.2% males, 80.3% females) responded that they experienced stress. Those who failed to stop smoking had higher odds of stress than those who did not attempt smoking cessation [odds ratio (OR) 1.11, 95% confidence interval (CI) 1.09-1.14, p < 0.001]. Those who successfully stopped smoking had lower odds of stress than those who did not attempt smoking cessation (OR 0.87, 95% CI 0.86-0.89, p < 0.001). Conclusion The study found an association between unsuccessful smoking cessation and stress level. As the result, people who failed smoking cessation showed higher stress. These data should be considered in health policy recommendations for smokers.